2021
DOI: 10.3389/fpsyg.2021.627834
|View full text |Cite
|
Sign up to set email alerts
|

Percentiles and Principal Component Analysis of Physical Fitness From a Big Sample of Children and Adolescents Aged 6-18 Years: The DAFIS Project

Abstract: Assessing physical fitness has emerged as a proxy of the health status of children and adolescents and therefore as relevant from a public health point of view. DAFIS is a project included in Plan Galicia Saudable (Healthy Galicia Plan) of the regional government of Galicia (Spain). DAFIS consists of an on-line software devoted to record the results of a standard physical fitness protocol carried out as a part of the physical education curriculum. The aims of this study were: to obtain normative values of phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 37 publications
1
9
0
2
Order By: Relevance
“…We found that both boys and girls had the worst SR performance at the age of 11 or 12 years. Iglesias-Soler et al (43) had similar findings to ours, but Zhang et al (18) found that the performance of SR increased with age. In our study, children and adolescents received a positive score when their fingertips exceeded the toes.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…We found that both boys and girls had the worst SR performance at the age of 11 or 12 years. Iglesias-Soler et al (43) had similar findings to ours, but Zhang et al (18) found that the performance of SR increased with age. In our study, children and adolescents received a positive score when their fingertips exceeded the toes.…”
Section: Discussionsupporting
confidence: 84%
“…We observed that a substantial number of boys scored 0 in the pull-ups test, such as 40% boys aged 13 years and 30% boys aged 14 years, suggesting that this test might not finely distinguish the arm muscle strength of boys. Therefore, its usefulness and future use in Chinese children and adolescents are questionable due to the lack of sensitivity in this test, and more accurate alternative tests, such as bent-arm hang/flexed-arm hang, are widely used in some countries and regions ( 16 , 35 , 40 , 43 , 45 , 46 ) might also be considered for use. Moreover, studies exploring the relationship between the performances of pull-ups and bent-arm hang/flexed-arm hang are needed in the future to fully use previous data.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike muscular fitness, both quantitative and qualitative analysis reflected that cardiorespiratory fitness was similar between prepandemic and pandemic measurements. A previously published principal component analysis of prepandemic DAFIS data [ 12 ] showed that body composition and muscular fitness accumulated most of their variability in the health-related fitness of children and adolescents. Therefore, it might be possible that cardiorespiratory fitness was less sensitive for detecting differences in physical fitness between the prepandemic and pandemic samples.…”
Section: Discussionmentioning
confidence: 99%
“…Speed–agility and cardiorespiratory fitness were evaluated by the 4 × 10 m SRT and 20 m SRT, respectively. Descriptions of all the procedures have been previously published [ 12 ] ( Figure 2 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation